Recent Update on Tocolytics for the Management of Preterm Labour (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Tocolysis is the relaxation of the pregnant uterus to postpone delivery. Tocolytics are a wide variety of agents used to suppress uterine contraction given when delivery would result in preterm birth. Preterm birth the most important single determinant of adverse outcome in terms of both survival and quality of life of baby. Although preterm birth is defined as being before 37 completed weeks most mortality and morbidity is experienced by babies born before 34 weeks. Prevention and treatment of preterm birth is important though it is not possible when labour is too advanced, cervix is dilated for more than 4 cm and prolongation of pregnancy is hazardous because of intrauterine infection, placental abruption, IUGR, lethal congenital anomaly, severe PIH, eclampsia, active vaginal bleeding or cardiac disease 1,2. The aim of this paper is to review available data about the tocolytics. The tocolytic therapy also helpful for getting time for the administration of dexamethasone/betamethasone, a glucocorticoid drug which greatly accelerates fetal lung maturity. There is no clear first line tocolytic agent 3,4. Various types of drugs are used, with varying success rates and side effects that includes calcium-channel blockers, ? adrenergic receptor agonists, magnesium sulphate, prostaglandin-synthetase inhibitors, oxytocin receptor antagonists. Their specific effects on myometrial contractility, their safety, their efficiency, doses, route of entry, and side effects profile for the mother and the fetus are presented. The main question which tocolytic should be administrated is discussed.Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 21-26